A case study exploring the “new literacies” during a fifth-grade electronic reading workshop - Larson, Eva Lotta Cecilia (Kansas State University, 2007)
In today’s classrooms, literacy instruction is undergoing tremendous transformations as new technologies demand new literacies. The purpose of this qualitative case study was to examine how integration of technology supports the emergence of new literacies, within the context of an electronic reading workshop in a fifth-grade classroom. The electronic reading workshop provided students multiple opportunities to response to e-books, both as readers and technology users. First, e-book tools allowed the participants to engage in a spontaneous response process as the plot unfolded. Second, students responded to teacher-constructed prompts in electronic literature response journals. Analysis of the journals revealed responses from three broad categories: 1) personal meaning making, 2) character and plot involvement, and 3) literary criticism. Third, students engaged in conversational response while participating in asynchronous message board discussions. The students composed and posted their own response prompts. Analysis of the message board transcripts suggested five types of student-constructed prompts: 1) experiential prompts, 2) aesthetic prompts 3) cognitive prompts, 4) interpretive prompts, and 5) clarification prompts. Virtual guide response projects provided a fourth opportunity for response to e-books. Working in groups, students created virtual guides to the literature in which they visually represented their personal interpretations of the e-books. The virtual guides were published as multi-modal PowerPoint presentations including sounds, images, animations, and hyperlinks. As students conceptualized, researched, published and presented their virtual guides to the literature, they used new literacies to fully exploit the potential of the available technologies. The electronic reading workshop provided a learning environment in which students interacted with each other as they made sense of and accessed the available information and communication technologies. In particular, socially constructed learning occurred through threaded discussions on an electronic message board and development of virtual guide response projects. Educators must be responsive to today’s learners. This study illuminated the expanded possibilities for integrating technology and literacy within the context of an electronic reading workshop. Findings of the study suggest technology integration supports the emergence of new literacies, while the new literacies support students’ utilization of available technologies.
Keywords: New literacies; Technology integration; Education, Elementary (0524); Education, Language and Literature (0279); Education, Technology (0710)